(3GdYed HGdUajMI GdRQbGdjIs - (3GHf GdRQbGdI , CHh ESMGb,J (B493 (3g` s
(3ChdgG (B:s
(3gPg GdCdg CLd GdBdGJ hCTQagG dYehegG LejY GdBaGb hGTQY GdBf ai JdNjU eG PcQg eDdagG ai GdYed HgG hJfbjMg hEJeGe eG fbU efg s
(3BNQgG (B:s
(3HYO hVY MQa GdYVGOI GdJi Ydi OGFQI GdCbWGH GdCQHYI Ydi Cab GdGSJhGA cJHfG CHYGO GdeOGQGJ Yf eOGQ GdESJhGA hGddg Gdehab ddUhGH hGdMeO ddg s
(3HChdgG Jedc HJGQjN SfI (B1127s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B79 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B128s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B194) s
Keywords: (3Gdadcs